2017
DOI: 10.1111/add.13766
|View full text |Cite
|
Sign up to set email alerts
|

Attrition during a randomized controlled trial of reduced nicotine content cigarettes as a proxy for understanding acceptability of nicotine product standards

Abstract: Aims To determine (1) if nicotine content affects study attrition – a potential behavioral measure of acceptability – in a trial that required compliance with three levels of reduced nicotine content (RNC) cigarettes, and (2) if attrition is associated with subjective and behavioral responses to RNC cigarettes. Design Secondary analysis of a 35-day, parallel design, open-label, randomized controlled trial. After a 5-day baseline period, participants were randomized to smoke for three, 10-day periods: their p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…In clinical trials, VLNCs generally have lower acceptability than commercially available cigarettes, and these trials have encountered problems with nonadherence (with upward of 70% of participants substituting traditional cigarette brands for VLNCs) and study dropout rates of 25 to 45% ( 229 , 230 ). Combining VLNCs with nicotine patches may aid with the transition to VLNCs and increase compliance, but doing so was not found to improve long-term quit rates.…”
Section: Discussion: What Evidence Is Neededmentioning
confidence: 99%
“…In clinical trials, VLNCs generally have lower acceptability than commercially available cigarettes, and these trials have encountered problems with nonadherence (with upward of 70% of participants substituting traditional cigarette brands for VLNCs) and study dropout rates of 25 to 45% ( 229 , 230 ). Combining VLNCs with nicotine patches may aid with the transition to VLNCs and increase compliance, but doing so was not found to improve long-term quit rates.…”
Section: Discussion: What Evidence Is Neededmentioning
confidence: 99%
“…Despite this, we were able to pick up where previous reviews left off, 10,11 thereby avoiding duplication of effort. Third, some studies in this review were limited by participant noncompliance or differential attrition, 20,67,73,74 and several studies reported on validation of measures to most accurately assess compliance in future studies. 20,67,71,74 Fourth, although an ultimate goal is to quantify risk of VLNCs, this initial paper was intended to provide an overview of the framework and the published literature, so future review of subsets of these data will be meta-analyzed where possible.…”
Section: Discussionmentioning
confidence: 99%
“…However, prior studies suggest concordance between estimates from hypothetical purchase tasks and consumption patterns. 18,2123 Regardless, future studies that test the predictive validity of the ETM will further delineate the utility of this novel approach. Prospective studies are required to see if this sophisticated method provides more accurate prediction of changing behavior than simpler methods such as simply asking the person how likely they are to use a product.…”
Section: Discussionmentioning
confidence: 99%
“…Product acceptability, as measured by study retention, was lower for smokers randomized to abruptly transition to VLNCs and for those who rated taste less favorably. 23 In the largest clinical trial of VLNCs, participants randomized to receive 6 weeks of VLNCs (≤ 2.4 mg/g) reported a reduction in estimated consumption of study cigarettes relative to those provided normal nicotine content cigarettes (15.8 mg/g). 21 Future studies should examine how ETM purchasing patterns change over time as a function of product use, which may improve the accuracy of substitution estimates.…”
Section: Discussionmentioning
confidence: 99%